Why should I consult? The impact of social support on patient consultation in online healthcare communities - Liu, Xiaochen; Xu, Zhen; Yu, Xintao; Oda, Tetsuaki (Frontiers in Psychology, 2022)
The COVID-19 epidemic put the traditional healthcare system and offline consultation method under strain. Patients' consultation on online healthcare communities (OHCs) provides patients and physicians with a more convenient and secure route. Based on the social support theory, this study explores the impact of three dimensions of physicians' social support (information diagnosticity, source credibility, and emotional support) on patients' consultation in OHCs, and the moderating effect of patients' compliments. We utilized python Spiders to retrieve data from Haodf.com and gathered 2982 physicians' data. Main models use the OLS regression with fixed effect estimations. The results show that the three dimensions of physicians' social support (information diagnosticity, source credibility, and emotional support) positively impact patients' consultation. Furthermore, patients' compliments weaken the positive relationship between three dimensions of physicians' social support and patients' consultation. This study contributes to the literature on social support theory in OHCs by exploring the physicians' social support dimension and its impact on patients' consultation. Moreover, this study has practical contributions to physicians and platform administrators in OHCs.